Metode Simple Moving Average dan Weighted Moving Average Dalam Memprediksi Produksi Beras - Darwati, Ida; Hayuningtyas, Ratih Yulia (Evolusi : Jurnal Sains dan Manajemen, 2023)
Many areas in Indonesian, rice is used as one of the daily staple foods, so it is important to pay attention to the amount of rice production. In this study the authors predict rice production in East Java Province, because increase population so the staple food of rice needs to be considered for the future. In overcoming, a supporting factor is needed for rice production and a prediction is needed to determine the amount of rice production must be achieved in the future. The rice production data used in this study is from January 2020 to Desember 2022. Prediction the amount of rice production, authors use two methods, that Simple Moving Average and Weighted Moving Average and then look for the smallest RMSE value, using the python programming language. The result study Weighted Moving Average method is the right method compared to the Simple Moving Average method in predicting rice production in East Java Province.